2012
DOI: 10.1111/j.1399-3054.2011.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

The IP amplitude of the fluorescence rise OJIP is sensitive to changes in the photosystem I content of leaves: a study on plants exposed to magnesium and sulfate deficiencies, drought stress and salt stress

Abstract: The hypothesis that changes in the IP amplitude of the fluorescence transient OJIP reflect changes in leaf photosystem I (PSI) content was tested using mineral-deficient sugar beet plants. Young sugar beet plants (Beta vulgaris) were grown hydroponically on nutrient solutions containing either 1 mM or no Mg(2+) and 2.1 µM to 1.88 mM SO(4)(2-) for 4 weeks. During this period two leaf pairs were followed: the already developed second leaf pair and the third leaf pair that was budding at the start of the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 33 publications
7
116
0
4
Order By: Relevance
“…The decrease of IP-amplitude is typical for drought stress [67]; however, in some species it occurs only at severe drought stress [68] and it disappears after rehydration [69]. Although the full interpretation of J-I-P kinetics is rather complicated [70,71], the IP amplitude was suggested to be a measure of relative abundance of PSI with respect to PSII [72,73], and its decrease was previously ascribed to decrease of PSI content in leaves [67,74]. In our experiment (Fig.…”
Section: Effects Of Drought Stress Analyzed By Simultaneously Recordesupporting
confidence: 43%
“…The decrease of IP-amplitude is typical for drought stress [67]; however, in some species it occurs only at severe drought stress [68] and it disappears after rehydration [69]. Although the full interpretation of J-I-P kinetics is rather complicated [70,71], the IP amplitude was suggested to be a measure of relative abundance of PSI with respect to PSII [72,73], and its decrease was previously ascribed to decrease of PSI content in leaves [67,74]. In our experiment (Fig.…”
Section: Effects Of Drought Stress Analyzed By Simultaneously Recordesupporting
confidence: 43%
“…in PSI (Schreiber et al 1989;Schansker et al 2003). The I-P phase seems to be related to the content of PSI reaction centers (Ceppi et al 2012) or availability of linear electron transport as determined by 820-nm transmission measurements (Zivcak et al 2014a). For example, the extent of the I-P loss in barley varieties depends on their drought tolerance (Oukarroum et al 2009;Ceppi et al 2012).…”
Section: Drought Stressmentioning
confidence: 99%
“…The I-P phase seems to be related to the content of PSI reaction centers (Ceppi et al 2012) or availability of linear electron transport as determined by 820-nm transmission measurements (Zivcak et al 2014a). For example, the extent of the I-P loss in barley varieties depends on their drought tolerance (Oukarroum et al 2009;Ceppi et al 2012). ChlF is emitted following a dark-to-light transition of a photosynthetic sample, while delayed fluorescence emission (DF) occurs during light-to-dark transitions (Goltsev et al 2009;Strasser et al 2010;Kalaji et al 2012).…”
Section: Drought Stressmentioning
confidence: 99%
“…Magnesium is essential for chlorophyll synthesis and up to 10 % of total Mg can be associated with chlorophyll (Wilkinson et al 1990). Furthermore, Mg is important for grana stacking in chloroplasts (Hall et al 1972;Ceppi et al 2012) that may adversely affect photosynthetic performance of plants suffering from low Mg supply. It was reported that the degree of stacking increases with increasing Mg concentrations (Stys 1995) and Mg deficiency leads to disruption of grana stacks (Hall et al 1972).…”
Section: Introductionmentioning
confidence: 99%